Constructing global carboniferous climatic fluctuations using high resolution geochronology - Pointon, Michael (Trinity College (Dublin, Ireland). Department of Geology, 2012)
The Carboniferous Period was a time of substantial climatic change, during which occurred the transition from a greenhouse (ice-free) environment into major continental glaciation. The onset of major Carboniferous glaciation is reconstructed using two main stratigraphic records: the direct records of glacial sedimentary rocks preserved on the remnants of Gondwana and far-field, ice-distal proxy records from palaeo-equatorial regions. Neither of these records provides a perfect account of the onset of major glaciation and there are conflicts regarding the timing of the onset of glaciation, both between the direct and indirect records and also within the indirect proxy records themselves. The aims of this project are three-fold: I) to constrain better the timing of the onset of major Carboniferous glaciation as recorded by the indirect, far-field records of western Europe using high precision U-Pb geochronology; 2) to constrain the periodicity of western European cyclic sedimentation, which has been interpreted to reflect the waxing and waning of Carboniferous ice sheets on southern Gondwana (glacio- eustasy); 3) to provide additional high-precision age constraints for the improved calibration of the Carboniferous timescale.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin